The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1007/s10637-018-0595-8
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy inhibition improves the chemotherapeutic efficacy of cruciferous vegetable-derived diindolymethane in a murine prostate cancer xenograft model

Abstract: Prostate cancer is the second leading cause of cancer-related deaths in men in North America and there is an urgent need for development of more effective therapeutic treatments against this disease. We have recently shown that diindolylmethane (DIM) and several of its halogenated derivatives (ring-DIMs) induce death and protective autophagy in human prostate cancer cells. However, the in vivo efficacy of ring-DIMs and the use of autophagy inhibitors as adjuvant therapy have not yet been studied in vivo. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…CQ, an antimalarial and anti-inflammatory drug, is one of the most prominent cases of drug repurposing in cancer [ 59 ]. Several reports and clinical trials have revealed the benefit of combining this compound with different chemotherapeutic drugs [ 9 , 11 , 12 , 13 , 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. In this study, we describe a synergistic effect between CQ and NHEJ inhibitors for the first time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CQ, an antimalarial and anti-inflammatory drug, is one of the most prominent cases of drug repurposing in cancer [ 59 ]. Several reports and clinical trials have revealed the benefit of combining this compound with different chemotherapeutic drugs [ 9 , 11 , 12 , 13 , 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. In this study, we describe a synergistic effect between CQ and NHEJ inhibitors for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CQ is considered a potential anticancer agent; it has been described to reduce hypoxia, cancer cell invasion, and metastasis [ 10 ]. Moreover, several preclinical results and clinical trials have shown that this compound, in combination with other antitumor drugs, increases the cytotoxic effect and sensitizes tumor cells to radiotherapy or chemotherapy [ 9 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. The effect of CQ as an anticancer drug has been mainly attributed to autophagy inhibition [ 9 , 12 , 13 , 14 , 21 , 22 , 23 ], a process that promotes cancer cell survival by recycling intracellular organelles and proteins [ 11 , 24 , 25 , 26 ], and it is considered a resistance mechanism against chemotherapy [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Xenotransplantation model is an ideal animal model for tumor research [51,52]. At present, xenografted mouse models have been established for PC, gastric cancer, breast cancer and other tumors, which maintained the pathological and histological characteristics of the original tumor from multiple perspectives such as histopathology and genetics [53][54][55][56]. In this study, the effects of FTX on PC tumor growth in vivo were investigated by establishing xenotransplantation mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Also, CQ treatment led to increased sensitization of prostate cancer cells to DIM treatment. Thus, DIM and CQ acted synergistically to inhibit prostate cancer [ 253 ].…”
Section: Combination Strategies—the Therapeutic Opportunitymentioning
confidence: 99%